Re-Evaluating Some of the Fundamental Educational Questions in Line with the Development in New Physics - Dundar, Selma (Journal of Research in Educational Sciences, 2013)
The purpose of the study is to understand whether the developments in physics after quantum theory can have an impact on educational sciences. Throughout the research quantitative paradigms was used. The qualitative data were obtained from a focus group consisted of 6 physicists working at CERN. The data were subjected to a content analysis and analyzed in 11 themes and 21 sub-themes under 4 global themes. With the help of obtained results, a discussion was conducted about the possible impacts of developments in physics after the quantum theory on the science of education, aiming to contribute to the philosophy of science in an educational framework. As a proposal for further research, the general framework of five periodic meetings was determined and it aims at bringing together experts from different disciplines such as physics, philosophy, education and art.